Block versus random: effective molecular configuration of copolymer gelators to obtain high-performance gel electrolytes for functional electrochemical devices. Issue 47 (12th November 2020) - Choi, Won Young; Kim, Yong Min; Ahn, Hyungju; Moon, Hong Chul
Abstract : In this work, we investigate the correlation between the molecular configuration of copolymer gelators and the resulting gel performance. Abstract : In this work, we investigate the correlation between the molecular configuration of copolymer gelators and the resulting gel performance. Two copolymers exhibiting phase homogeneity without noticeable phase separation, poly(ethyl methacrylate)- ran -polystyrene (PEMA- r -PS) and disordered PEMA- b -PS, are prepared as gelators. To ensure an accurate comparison, factors closely related to gel properties ( e.g., total molecular weight of gelators, styrene fraction of both copolymers, and gel composition) were fixed. Both gelators produce ion gels with similar conductivities when blended with an ionic liquid of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMI][TFSI]). However, there is a significant difference in their mechanical robustness. For example, the elastic modulus (∼2.20 × 10 5 Pa) of PEMA- r -PS-based gels was ∼113% higher than that (∼1.03 × 10 5 Pa) of the gel containing PEMA- b -PS. This result is explained by the difference in gel network structure. Namely, PEMA- r -PS gels contain a high density of smaller [EMI][TFSI]-insoluble styrene domains, which are advantageous for obtaining mechanically robust ion gels without sacrificing ionic conductivity. Moreover, the versatility of PEMA- r -PS gels as an electrochemical platform is demonstrated via application in electrochromic devices and stretchable ionic motion sensors. Overall, this work suggests that tuning the molecular configuration of copolymer gelators is another effective way to obtain high-performance ion gel electrolytes for various electrochemical applications.